Multivariate factor analysis (MFA) approach to evaluate the quality of stored Cavendish banana sourced from different geographical areas - Giuggioli, Nicole Roberta; Peano, Cristiana; Da Silva, Thais Mendes (Emirates Journal of Food and Agriculture, 2020)
The Multiple Factor Analysis (MFA) was applied to assess deterioration patterns and evaluate quality stability of bananas samples with 5 different origins. Quality evaluation (weight loss, dry matter, colour, total soluble solids, texture and nutraceutical analysis) was conducted at 21°C for up to 12 days of storage time. Ecuador samples retained a better colour and firmer texture during shelf life while Cameroon samples demonstrated very poor quality for almost all quality indicators. Although MFA showed a similar shelf life pattern for all banana samples, it was possible to observe a greater quality retention of Ecuador samples, represented by higher score values at dimension 1 than other samples. Even though there were significant differences of nutraceutical values during shelf life, the MFA contribution plot demonstrated that nutraceutical quality was not a good indicator of deterioration among the samples, especially with texture and colour parameters.